Investigation of wind energy generation by moving vehicles in Uniten - Chua Y.L.; Asokan N.; Koh Y.Y. (American Institute of Physics Inc., 2023)
The purpose of this paper is to investigate the amount of wind energy that can be generated by moving vehicles in and around Universiti Tenaga Nasional (UNITEN). This paper aims to harvest wind movement produced by moving vehicles and calculate how much of that energy can be converted to electrical energy. Various forms of research and experimentation have been done throughout the time period of this project which includes research regarding the importance of renewable energy, the development state of Malaysia in the renewable energy field, the various forms of renewable energy, the potential of wind energy in Malaysia, the types and applications of wind turbines in harvesting wind energy from a variety of sources such as journals, websites and articles. As for the experimentation part of this project, wind speed readings at various locations and various heights were recorded while a wind turbine prototype was designed, fabricated and field tested in and around UNITEN. This project emphasizes on the readings obtained from the prototype field test and output power generated from moving vehicles. 2019 Author(s).